USER INTERFACE TESTING SEBAGAI LANGKAH MEMINIMALISIR RISIKO DIGITALISASI SARANA PRASARANA SEKOLAH - Komarudin Tasdik; Anggia Rabiyah Al-Adawiyah; Bambang Subeno (PROGRESS, 2025)
User Interface (UI) design is one of the current specialized jobs so that there are special vacancies for the profession of UI designer. Along with this phenomenon, there are still schools that do not have a mobile application to facilitate their management, including asset data management. This study aims to add references on UI design along with how to test the design that can be implemented by programmers more easily. The design testing process is carried out using usability testing. Usability measurements are carried out on three parameters, namely effectiveness, efficiency, and satisfaction. The results obtained that as one of the solution recommendations, a mobile prototype was designed with the main features including the Borrow Page and Asset Borrowing Form. From the results of testing the prototype, the results obtained that the prototype that had been created obtained an Effectiveness aspect value of 100%, Efficiency of 0.152 goals/sec, and a SUS Score of 92 (Best Imaginable).